COWHIDE GELATIN NANOPARTICLES AND TITANIUM-PREPARED PLATELET-RICH FIBRIN POTENTIAL IN PERIODONTITIS HEALING PROCESS - Kurniawati, Atik; Saputra, Dwi Riski; Sari, Dewi Yunita; Amanitha, Indhi Cinthiya; Masruroh Hariyati, Siti Nurul (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Introduction: Based on epidemiological data, the periodontitis prevalence in Indonesia reached 96.58%. Periodontitis is a periodontal disease caused by specific microorganisms causing attachment loss, alveolar bone resorption, and periodontal pocket. The pocket which is more than 6 mm couldn’t be carried out using standard care. Therefore bone grafting is needed to fix the bone defect. Cowhide Gelatin nanoparticle (GNPs) combined with Titanium-Prepared Platelet-Rich Fibrin (T-PRF) is an innovative healing of periodontitis. Objective: To review the potential of cowhide gelatin nanoparticles combined with titanium-prepared platelet-rich fibrin (T-PRF) as an innovation in the healing of periodontitis defects. Literature review: Cowhide GNPs are the main ingredients for the bone replacement, which are nano-sized, biocompatible, bioactive, osteoconductive, non-toxic, and have a porous structure that supports the drug-delivery process. T-PRF contains platelets, fibrin, growth factors that can stimulate bone regeneration. Discussion: GNPs support the attachment and proliferation of osteoblast cells and the formation of mineralized bone matrix. The contents of T-PRF, which are fibrin, platelets, and growth factors, one of TGF-β1 will produce bone formation and periodontal healing in the large number. Moreover, T-PRF has leukocyte-fibrin, which may give an antibacterial effect. Thus, GNPs combined with T-PRF have more potent properties that support each other in carrying out their functions to stimulate the healing process. Conclusion: The combination of cowhide gelatin nanoparticles (GNPs) and titanium-prepared platelet-rich fibrin (T-PRF) has the potential to be effective in bone regeneration in periodontitis defects.